Assessment of needs and barriers to sex and gender education among social workers in Egypt - Riad, Germeen (AUC Knowledge Fountain, 2019)
Despite governmental and legislative efforts (Hassanin, 2008), societal tolerance of sexual and gender-based violence is widespread in Egypt, even among health professionals (Rasheed, 2011). Moreover, there is a lack of understanding and misconceptions regarding human sexuality. Such misconceptions often lead to harmful practices such as female genital mutilation/cutting, childhood marriage, and child sexual abuse (WHO, 2010). Child protection social workers must be equipped to deal with children who have been victims of such practices and must be able to provide the sex education that is necessary for its prevention. A survey of 86 child protection social workers and eleven in-depth interviews was conducted in order to better understand how they viewed and dealt with sexuality, gender roles and sexual and gender-based violence. It was found that they had a number of misconceptions about sexuality as well as a tendency to gender stereotype. Female social workers were overall less tolerant of gender-based violence, more supportive of gender equality and had fewer misconceptions related to sex compared to male social workers. Male social workers who were married were more likely to hold attitudes supportive of women facing sexual and gender-based violence, had more flexible views of gender roles and lower double standards, and were more open to gender equality, than male social workers who were single. Based on these results, recommendations are made for culturally appropriate training to build social workers' capacity for addressing sex and gender issues in their child protection practice.